2021
DOI: 10.1093/ajcn/nqaa258
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity and mortality in Korean adults: a population-based prospective cohort study

Abstract: Background The Asia-Pacific obesity classification recommends using lower BMI cutoffs in Asians compared with those in Western populations. However, the supporting evidence is scarce and little is known about the exact shape of the relations between adiposity and mortality in Asians. Objectives We investigated the relations of BMI (in kg/m2), waist circumference, and predicted body fat mass with mortality using a population-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…The J‐shaped relationship between BMI and mortality has been reported across the diverse population. 48 In the Korean population, the lowest mortality rate was observed in obese subjects (25–29.9 kg/m 2 ), 49 , 50 which suggests that among the Korean population with BMI < 30 kg/m 2 , there might be an inverse association between their BMI and mortality rate. In addition, Asians have a relatively higher proportion of non‐obese NAFLD, which exhibits distinct metabolic features and genetic alterations in PNPLA3 and TM6SF2 compared with obese NAFLD in Western population.…”
Section: Discussionmentioning
confidence: 98%
“…The J‐shaped relationship between BMI and mortality has been reported across the diverse population. 48 In the Korean population, the lowest mortality rate was observed in obese subjects (25–29.9 kg/m 2 ), 49 , 50 which suggests that among the Korean population with BMI < 30 kg/m 2 , there might be an inverse association between their BMI and mortality rate. In addition, Asians have a relatively higher proportion of non‐obese NAFLD, which exhibits distinct metabolic features and genetic alterations in PNPLA3 and TM6SF2 compared with obese NAFLD in Western population.…”
Section: Discussionmentioning
confidence: 98%
“…As per statistical analysis, there was a solid clinical association between obesity and Type-2 DM [15].…”
Section: Resultsmentioning
confidence: 94%
“…Forty‐nine articles with 66 reports reported muscle wasting‐related effect sizes for mortality risks due to all causes, 16–20,37–79 eight articles with 11 reports due to CVD, 45,49,51,55,61,65,68,74 three articles with 4 reports due to cancer, 51,61,65 three articles with 4 reports due to respiratory disease 51,61,68 and one article with 2 reports due to diabetes 55 . No available information was found for mortality from other causes.…”
Section: Resultsmentioning
confidence: 99%
“…The sample size ranged from 191 to 405 980. The total number of deaths was 61 055 (one trial not reported 46 ), 7520 (two trials not reported 51,65 ), 3726 (two trials not reported 51,65 ), 3537 (one trial not reported 51 ) and 107 from all causes, CVD, cancer, respiratory disease and diabetes, respectively. The mean age of participants ranged from 38.7 to 93.5 years.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%